دور القرآن الكريم في تحقيق الأمن النفسي : ‏ دراسة مقارنة بين القرآن الكريم وعلم النفس - قاسمي، زهراء (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This research conducts a comparative and analytical study on the psychological security between the Qur'an and psychology by exploring the concept of psychological security and its characteristics. The research focuses on the concept of mental disorder, its causes and effects, and further explores similarities and differences from both perspectives (the Qur'an and psychology). The research also addresses the impact of the lack of psychological security on the individual and family. The research adopted the inductive and comparative approaches. Both approaches help to discover the sound method in deducing the features of psychological security on the basis of the Qur'an and its higher objectives. The research has introduced preventive and treatment measures of psychological anxiety disorders and behavioral deviations, and concluded that the Holy Qur'an pays attention to systematic guidelines on psychological security through faith, rituals and moral obligations, while psychology relies more on material values and traditions. The research adds further evidence how real psychological security could not be attained unless accompanied with spiritual guidance as found in Islam.